Membangun Budaya Tertib Lalu Lintas di Kalangan Pelajar: Studi Pengabdian di MA Plus Nururrohmah - Rahmatullah, Azam Syukur; Kencono , Dewi Sekar; Harianto, Eko (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Traffic discipline remains a significant challenge among students, particularly at the secondary school level. To address this issue, a community service team from Universitas Muhammadiyah Yogyakarta conducted a program at MA Plus Nururrohmah. The objective was to instill traffic awareness and discipline through educational and participatory approaches. The methods included interactive seminars, safety riding training, and student role simulations as school traffic officers. The program engaged students, teachers, staff, and external stakeholders such as the police. The results indicated substantial improvements in students’ traffic knowledge, attitudes, and behavior, including consistent helmet use and organized parking. This program demonstrates that participatory school-based traffic education can effectively foster a culture of safety among students